2013
DOI: 10.1371/journal.pone.0067743
|View full text |Cite
|
Sign up to set email alerts
|

Prion Peptide Uptake in Microglial Cells – The Effect of Naturally Occurring Autoantibodies against Prion Protein

Abstract: In prion disease, a profound microglial activation that precedes neurodegeneration has been observed in the CNS. It is still not fully elucidated whether microglial activation has beneficial effects in terms of prion clearance or whether microglial cells have a mainly detrimental function through the release of pro-inflammatory cytokines. To date, no disease-modifying therapy exists. Several immunization attempts have been performed as one therapeutic approach. Recently, naturally occurring autoantibodies agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 53 publications
(63 reference statements)
0
14
0
Order By: Relevance
“…Interestingly, CpG post-immune sera decreased the conversion activity of CWD prions in RT-QuIC assay only very marginally, much less than the blocking effect caused by Mdi and Ddi post-immune sera at the identical dilution. The subtle effect of control sera may be explained, at least partially, by the existence of some autoantibodies against PrP as reported by previous studies 41 , 42 . Whether using deer or mouse substrate did not affect the inhibitory effect of post-immune sera (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…Interestingly, CpG post-immune sera decreased the conversion activity of CWD prions in RT-QuIC assay only very marginally, much less than the blocking effect caused by Mdi and Ddi post-immune sera at the identical dilution. The subtle effect of control sera may be explained, at least partially, by the existence of some autoantibodies against PrP as reported by previous studies 41 , 42 . Whether using deer or mouse substrate did not affect the inhibitory effect of post-immune sera (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…The analysis of ThioT-positive areas of microglia-depleted OHSCs following Aβ 1-42 treatment for 48 h did not result in a significant difference compared to non-treated OHSCs ( Figure 5C). In contrast, significant increases in hippocampal areas positive for ThioT were observed To further investigate the impact of microglial Aβ 1-42 uptake on neuronal survival in OHSCs, we applied cytochalasin D, a blocker of actin polymerization that inhibits the phagocytic activity of microglia (64,74) at a concentration that was barely neurotoxic in OHSC (52). Treatment with cytochalasin D resulted in a significant increase in the hippocampal area that was positive for ThioT, suggesting efficient inhibition of microglial Aβ 1-42 intake ( Figure 5D).…”
Section: Phagocytosis Of Aβ 1-42 Contributes To the Neuroprotective Ementioning
confidence: 99%
“…For ELISA and ThT assays monomeric Aβ was used. For PrP experiments, a short fragment of the prion protein with a single mutation (PrP106-126 A117V), was applied, which was successfully used previously in aggregation studies and already showed oligomerization [ 30 , 13 , 24 ]. Furthermore, this PrP version exhibits some pathological characteristics of PrP sc , like fibril formation [ 31 ].…”
Section: Methodsmentioning
confidence: 99%